Validation of the self-applicable version of the Resilience Subscale of the BESSI-45 Inventory in Peruvian adolescents aged 12 to 17 years - Vega-Dienstmaier, Johann Martín (2024)
Introduction: Emotional resilience skills involve the regulation of stress, anxiety, fear, anger, and irritability; intentional impulse resistance; and maintaining a positive attitude towards difficult circumstances and oneself. The aim of this study is to assess the psychometric properties of a Spanish version of the resilience subscale of the BESSI-45. Method: The BESSI-45 was administered to 625 adolescents from three different regions of Peru. The resilience subscale was evaluated in terms of norms, internal consistency, factorial structure, factorial invariance, and item response theory (IRT)-based characteristics. Results: Internal consistency was adequate (omega = 0.8243), the factor analysis showed a unidimensional structure with good fit indices, and factorial invariance was demonstrated across gender and geographic region. The discrimination ability according to IRT was satisfactory for all items. The most important items were three that were related to anger control and impulsivity. Conclusion: The resilience subscale of the BESSI-45 demonstrates good characteristics in the evaluated sample of Peruvian adolescents.